Simulation of the Transmission by Vectors of Bluetongue Disease and Analysis of the Control Strategy - Đurić Spomenka (Sciendo, 2018)
Bluetongue disease is an infectious non-contagious disease of domestic and wild ruminants, transmitted by hematophagous insects of the genus Culicoides. In endemic areas the disease has a seasonal character, occurs usually in summer when the population of vectors is at its peak. Culicoides are active at temperatures in the range from 13oto 35oC. The replication of the virus stops when the environmental temperature is below 13oC. It has been reported that the temperature and humidity of the environment affect to a great extent the biology of the vector and the survival of the virus in the reservoirs. During the summer, the number of infected cattle and sheep is directly dependent on the density of the population of the vector, the length of vectors’ life-span, the temperature of the environment and by precipitation, the affi nity of the vector to different hosts, and the ability of the vector to locate the host. Bluetongue has been spreading worldwide due to climatic changes and increasing average daily temperatures. The seasonal occurrences of the disease and the climate change have conditioned the need for adopting new strategies. The stochastic SEIRD mathematical model has been developed in order to simulate the transmission of the Bluetongue virus through the susceptible ruminant population on the territory of the Republic of Serbia, as well as to investigate the effect of climatic factors on the vector population and the magnitude of a possible epizootia. Besides the effects of climatic factors, we have analyzed a number of different approaches in the control of the disease based upon the vaccination of ruminants and control of vectors.